One-step detection of circulating tumor cells in ovarian cancer using enhanced fluorescent silica nanoparticles - Kim JH (International Journal of Nanomedicine, 2013)
Jin Hyun Kim,1,* Hyun Hoon Chung,2,* Min Sook Jeong,1 Mi Ryoung Song,1 Keon Wook Kang,3,4 Jun Sung Kim1 1R&D Center, Biterials Co, Ltd, Seoul, Republic of Korea; 2Department of Obstetrics and Gynecology, Seoul National University College of Medicine, Seoul, Republic of Korea; 3Department of Nuclear Medicine, Seoul National University College of Medicine, Seoul, Republic of Korea; 4Cancer Research Institute, Seoul National University, Seoul, Republic of Korea *These authors contributed equally to this work Abstract: Ovarian cancer is the fifth-leading cause of cancer-related deaths among women as a result of late diagnosis. For survival rates to improve, more sensitive and specific methods for earlier detection of ovarian cancer are needed. This study presents the development of rapid and specific one-step circulating tumor cell (CTC) detection using flow cytometry in a whole-blood sample with fluorescent silica nanoparticles. We prepared magnetic nanoparticle (MNP)-SiO2(rhodamine B isothiocyanate [RITC]) (MNP-SiO2[RITC] incorporating organic dyes [RITC, λmax(ex/em) = 543/580 nm]) in the silica shell. We then controlled the amount of organic dye in the silica shell of MNP-SiO2(RITC) for increased fluorescence intensity to overcome the autofluorescence of whole blood and increase the sensitivity of CTC detection in whole blood. Next, we modified the surface function group of MNP-SiO2(RITC) from –OH to polyethylene glycol (PEG)/COOH and conjugated a mucin 1 cell surface-associated (MUC1) antibody on the surface of MNP-SiO2(RITC) for CTC detection. To study the specific targeting efficiency of MUC1-MNP-SiO2(RITC), we used immunocytochemistry with a MUC1-positive human ovarian cancer cell line and a negative human embryonic kidney cell line. This technology was capable of detecting 100 ovarian cancer cells in 50 µL of whole blood. In conclusion, we developed a one-step CTC detection technology in ovarian cancer based on multifunctional silica nanoparticles and the use of flow cytometry. Keywords: circulating tumor cells, CTCs, fluorescent nanoprobe, MUC1, ovarian cancer